Initial prevalence of anal human papilloma virus infection in liver transplant recipients. (24th May 2014) - Grąt, Michał; Grąt, Karolina; Hołówko, Wacław; Malejczyk, Magdalena; Walter de Walthoffen, Szymon; Lewandowski, Zbigniew; Kobryń, Konrad; Patkowski, Waldemar; Majewski, Sławomir; Młynarczyk, Grażyna; Krawczyk, Marek
Summary Although liver transplant recipients are at increased risk of human papilloma virus (HPV)‐related anal cancer, limited data are available regarding the initial prevalence of anal HPV infection in this population. Anal swabs collected from 50 liver transplant recipients within the first three postoperative weeks were subjected to real‐time polymerase chain reaction for detection of the four HPV genotypes: 6, 11, 16, and 18. Predictors of any, low‐risk, and high‐risk anal HPV infection were evaluated. Overall, the prevalence of any anal HPV infection was 18.0%, with the corresponding rates for high‐ and low‐risk HPV genotypes being 8.0% and 10.0%, respectively. Infection with any type of anal HPV was higher in patients with hepatitis B virus (HBV) infection (P = 0.027), ≥3 sexual partners (P = 0.031), and alcoholic liver disease (P = 0.063). HBV infection was the only factor significantly associated with high‐risk HPV infection (P = 0.038). Male sex (P = 0.050), age ≥52 years (P = 0.016), ≥30 sexual partners (P = 0.003), age at first intercourse ≤18 years (P = 0.045), and time since first intercourse ≥38 years (P = 0.012) were identified as predictors of low‐risk HPV infection. These results indicate that HPV vaccination of liver transplant candidates and screening for anal HPV infection in high‐risk groups should be considered.